Concept Of Oral Health In Ayurveda : A Review Article - Dansena, Gulshan; Fiaz, Shamsa; Bhatnagar, Sharad (International Research Journal of Ayurveda & Yoga, 2021)
Ayurveda is an ancient science of health and longevity. Oral infections are big public health problem around the world. Over hundreds to thousands of years of use, the herbs mentioned in the Ayurvedic material medica have been proven to be healthy and reliable. The study of plants used in traditional medicine may lead to the creation of new oral health preventive and therapeutic strategies. Ayurveda is an ancient science of health and longevity. Ayurveda’s Shalakya Tantra includes dentistry, despite the fact that it is not a specialist branch. In ancient India, problems including oral deformities, plaques, and infections were treated by using these drugs. Several systemic diseases are said to be cured by the Kavala and Gandoosh kriyas. Ayurveda oral health activities can be scientifically validated, allowing them to be incorporated into modern dental care. A study of various herbal plants and procedures listed in Ayurveda that can be used as an adjunct for the maintenance of oral health has been attempted in this paper.